Interleukins Affect Equine Endometrial Cell Function: Modulatory Action of Ovarian Steroids - Szóstek, Anna Z. (Hindawi Publishing Corporation, 2014)
The aim of the present study was to investigate the interaction between ovarian steroids, interleukins and prostaglandins (PG) in equine epithelial and stromal cells in vitro. In Experiment 1, cells were exposed to IL-1α (10 ng/mL), IL-1β (10 ng/mL) or IL-6 (10 ng/mL) for 24 h and cell proliferation was determined using MTT. In Experiment 2, cells were exposed to progesterone (P(4); 10(−7) M); 17-β estradiol (E(2); 10(−9) M) or P(4)+E(2) for 24 h and later medium was replaced with a fresh one treated with IL-1α, IL-1β or IL-6 (10 ng/mL, each) for 24 h. The oxytocin (OT; 10(−7) M) was used as a positive control. In Experiment 3, cells were exposed to P(4) (10(−7) M), E(2) (10(−9) M) or P(4)+E(2) for 24 h and the IL receptor mRNAs transcription was determined using Real-time PCR. Prostaglandins concentration was determined using the direct enzyme immunoassay (EIA) method. Our findings reveal a functional linking between ovarian steroids and IL-stimulated PG secretion by equine endometrial cells. This interaction could be one of the mechanisms responsible for endometrial local orchestrating events during the estrous cycle and early pregnancy.